Repetitive DNA sequences and evolution of ZZ/ZW sex chromosomes in characidium (teleostei: characiformes) - Scacchetti, Priscilla Cardim [UNESP]; Utsunomia, Ricardo [UNESP]; Pansonato-Alves, José Carlos [UNESP]; Silva, Guilherme José da Costa [UNESP]; Vicari, Marcelo Ricardo; Artoni, Roberto Ferreira; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Public Library Science, 2015)
Characidium constitutes an interesting model for cytogenetic studies, since a large degree of karyotype variation has been detected in this group, like the presence/absence of sex and supernumerary chromosomes and variable distribution of repetitive sequences in different species/populations. In this study, we performed a comparative cytogenetic analysis in 13 Characidium species collected at different South American river basins in order to investigate the karyotype diversification in this group. Chromosome analyses involved the karyotype characterization, cytogenetic mapping of repetitive DNA sequences and cross-species chromosome painting using a W-specific probe obtained in a previous study from Characidium gomesi. Our results evidenced a conserved diploid chromosome number of 2n = 50, and almost all the species exhibited homeologous ZZ/ZW sex chromosomes in different stages of differentiation, except C. cf. zebra, C. tenue, C. xavante and C. stigmosum. Notably, some ZZ/ZW sex chromosomes showed 5S and/or 18S rDNA clusters, while no U2 snDNA sites could be detected in the sex chromosomes, being restricted to a single chromosome pair in almost all the analyzed species. In addition, the species Characidium sp. aff. C. vidali showed B chromosomes with an inter-individual variation of 1 to 4 supernumerary chromosomes per cell. Notably, these B chromosomes share sequences with the W-specific probe, providing insights about their origin. Results presented here further confirm the extensive karyotype diversity within Characidium in contrast with a conserved diploid chromosome number. Such chromosome differences seem to constitute a significant reproductive barrier, since several sympatric Characidium species had been described during the last few years and no interespecific hybrids were found.